Muscle damage, endocrine, and immune marker response to a soccer match - Thorpe, R.; Sunderland, C. (The Journal of Strength and Conditioning Research, 2012)
This study represents the first time that muscle damage, endocrine, and immune markers have been measured, together with activity profile, during a competitive soccer match. Seven semiprofessional soccer players participated in a competitive league match. Blood and saliva samples were obtained 1 hour before kick off and immediately postmatch. Global positioning system equipment was used to measure heart rate and activity profile data throughout the match. Percentage increase in creatine kinase (CK) and myoglobin (MYO) concentrations was correlated with the number of sprints performed during the match (r = 0.88, p = 0.019; r = 0.75, p = 0.047, respectively). Creatine kinase increased by 84% (p = 0.17) from prematch to postmatch, whereas MYO increased by 238% (p = 0.05). Players performed 39 ± 18 sprints during the course of the match. Cortisol increased by 78% (p = 0.103), whereas testosterone increased significantly by 44% (p = 0.004). No differences were seen from prematch to postmatch in the testosterone to cortisol ratio, immunoglobulin (Ig) A, IgM, or IgG. Sprinting is correlated with changes in CK and MYO and may therefore be associated with muscle damage in semiprofessional soccer players.